Revision of Leocrates Kinberg, 1866 and Leocratides Ehlers, 1908 (Annelida, Errantia, Hesionidae) - Salazar-Vallejo, Sergio I. (Zootaxa, 2020)
Leocrates Kinberg, 1866 and Leocratides Ehlers, 1908 are two genera of hesionid errant annelids (Hesionidae, Hesioninae) whose species have 16 chaetigers (21 segments). Leocrates species are free living in rocky or mixed bottoms, whereas Leocratides species are usually symbiotic with hexactinellid sponges. Marian Pettibone revised both genera as part of the R/V Siboga Expedition monographs 50 years ago, and most of her ideas have remained unchallenged regarding synonymy for genera and species. For example, she included three genera as junior synonyms of Leocrates: Lamprophaes Grube, 1867, Tyrrhena Claparède, 1868, and Dalhousia McIntosh, 1885, and from 21 nominal species, she regarded only eight as valid. In this revision, all material available was studied, and different morphological patterns were noted in nuchal organs lobes, pharynx armature, and chaetal features. Leocratides species belong to a single pattern; however, in Leocrates several patterns were detected. Three patterns are present for nuchal organs lobes: barely projected posteriorly (horizontal C-shaped), markedly projected posteriorly (U-shaped), and with lateral transverse projections (L-shaped). In the pharynx, upper jaws were noted as single, fang-shaped, or as double, T-shaped structures, whereas the lower jaw can be single, fang-shaped, or a transverse plate. Neurochaetal blades can be bidentate with guards approaching subdistal tooth, unidentate without guards, or with guards hypertrophied projected beyond distal tooth. The combinations of these features are regarded as different genera and consequently, Leocrates is restricted (including Tyrrhena), but Dalhousia, and Lamprophaea (name corrected) are reinstated, and three new genus-group names are proposed: Paradalhousia n. gen., Paralamprophaea n. gen., and Paraleocrates n. gen. Further, the standardization of morphological features allowed several modifications and the recognition of novelties. Thus, four type species were redescribed, four others were reinstated, 10 were newly combined, and 18 from different World localities are described as new. The new species are Lamprophaea cornuta n. sp. from the French Polynesia, L. ockeri n. sp. from the Hawaiian Islands, L. paulayi n. sp. from the Red Sea, L. pettiboneae n. sp. from the Marshall Islands, L. pleijeli n. sp. from La Réunion, L. poupini n. sp. from the French Polynesia, Leocrates ahlfeldae n. sp. from India, L. harrisae n. sp. from the Revillagigedo Islands, L. mooreae n. sp. from New Caledonia, L. reishi n. sp. from the Marshall Islands, L. rizzoae n. sp. from the Seychelles Islands, L. rousei n. sp. from Papua New Guinea, L. seidae n. sp. from the French Polynesia, Leocratides jimii n. sp. from Madagascar, Paralamprophaea bemisae n. sp. from the Maldives, P. crosnieri n. sp. from Madagascar, P. leslieae n. sp. from Kiribati, and P. meyeri n. sp. from the French Polynesia. However, Leocrates japonicus Gustafson, 1930 is a nomen nudum. Keys are included for identifying all hesioninae genera, and for all species in all the included genera.